New perspectives on the human occupation of the Gulf of Palermo during the Metal Ages: the funerary cave of Zubbio di Cozzo San Pietro (Bagheria) and the necropolis of Viale Venere (Mondello, Palermo). (June 2020) - Battaglia, Giuseppina; Miccichè, Roberto M.; Forgia, Vincenza; Mannino, Marcello A.; Scopelliti, Maria Giuseppa; Sineo, Luca; Valenti, Pietro
Abstract: The Archaeological Superintendency of Palermo (Sicily), with the chair of Anthropology at the University of Palermo, carried out a preliminary investigation in the Zubbio of Cozzo San Pietro (Bagheria) – a cave known so far only from a speleological point of view - which proved to be a funerary cave dating to the Copper/Bronze Age. In the course of archaeological work during the installation of the electricity grid in the Mondello area (Palermo), part of a necropolis consisting of three oven-shaped tombs was exposed. The tombs multiple depositions, whose remains were found in a very bad state of preservation. Based on the type of funerary structures and the equipment found in them, we hypothesize the existence of a necropolis datable to the Early Copper Age that occupies a large area. After an articulated presentation of both necropolises, thanks to a multidisciplinary approach, an attempt was made to re-read all the elements available for a reconstruction of the Conca d'Oro (Palermo, Italy), during the metal ages.